2019
DOI: 10.1021/jacs.8b10083
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Polymer-Assisted Mesoscale Self-Assembly of Colloidal CsPbBr3 Perovskite Nanocrystals into Higher Order Superstructures with Strong Inter-Nanocrystal Electronic Coupling

Abstract: Surface passivating ligands, although ubiquitous to colloidal nanocrystal (NCs) synthesis, play a role in assembling NCs into higher-order structures and hierarchical superstructures, which has not been demonstrated yet for colloidal CsPbX3, (X= Cl, Br, and I) NCs. In this work, we report that functional polyethylene glycols (PEG6-Y, Y =-COOH and-NH2) represent unique surface passivating ligands enabling the synthesis of near uniform CsPbBr3 NCs with diameters of 3.0 nm. The synthesized NCs are assembled into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 93 publications
(190 reference statements)
0
54
0
Order By: Relevance
“…28 Plenty of effort has been devoted towards integration of perovskite NCs into numerous polymers, silica and other crystalline materials, but, so far, the porous MOG matrix has never been used to host perovskite NCs. [29][30][31][32] Therefore, porous MOG would be a new addition as a host matrix for encapsulating perovskite NCs.…”
Section: Introductionmentioning
confidence: 99%
“…28 Plenty of effort has been devoted towards integration of perovskite NCs into numerous polymers, silica and other crystalline materials, but, so far, the porous MOG matrix has never been used to host perovskite NCs. [29][30][31][32] Therefore, porous MOG would be a new addition as a host matrix for encapsulating perovskite NCs.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, synthesis of large‐sized perovskite nanocrystals has been proved to be a straightforward and empirically reliable strategy . For instance, Sardar obtained ordered perovskite superstructures with strong inter‐crystal electronic coupling using flexible polymer‐assisted self‐assembly of CsPbBr 3 nanocrystals; Tian and Rogach realized spontaneous assembly of CsPbBr 3 into cuboid crystals with high intensity blue emission; Sargent and Bakr reported halogen vacancies‐enabled ligand‐assisted self‐assembly of PQDs into nanowires, as well as CsPbBr 3 nanowires with sharp photoluminescence; Moreover, 1‐dimensional CsPbBr 3 superlattice chains were synthesized by hot‐injection method, and the stability of nanocrystals was improved due to collective properties from the nanosheet unit . The above studies have indicated that surface chemistry of PQDs, or more specifically the use or not and the type of capping ligands selected, have played a very critical role in obtaining large‐sized perovskites.…”
Section: Methodsmentioning
confidence: 99%
“…Nanocubes of CsPbBr 3 have a tendency to fuse into single crystals, 33 36 making them ideally suited for a self-assembled thin film and luminescent nanopatterned devices. However, the major problem behind their self-assembly is that due to their ionic nature they readily dissolve in a polar environment, while in a nonpolar solvent, they have a tendency to cluster 37 due to strong vdW attractions between the long capping ligands. Therefore, preventing colloidal aggregation to enable close-packed monolayer thin films remains an open challenge.…”
Section: Introductionmentioning
confidence: 99%